Review on Mobile Application for E-Land Information System - Gaikwad, Meghana; Choudhari, Sachin; Gulhane, Monali (International Journal of Computer Sciences and Engineering, 2025)
The proposed system describes “penetration of mobile phones has been incredible and has reached every nook and the corner of the country and has laid the foundation for economic growth, social empowerment and grassroots innovations. Mobile phone has permanently transformed the socio economic strata of the society. Mobile phone has allowed a lot of application to be developed and implemented for the benefit of the society. The smart phones have opened a plethora of opportunities and one such area is the land office which caters to provide and regulate the details of land, its sale and purchase etc. A mobile application can be developed which allows the smart phone user to obtain the land record and the details of the owner’s that to at the touch of the finger. This application can simplify the land office functioning and allows the user to get the information about the land at the comfort of his home instead of going to the land record office and struggle to get a piece of information”. Mobile communication technology has quickly become the world’s most common way of transmitting voice, data, and services in the developing world and given this change the mobile applications (Android Apps) in general have a tremendous potential to provide access to information to millions of people that to in a hassle free manner. The mobile system has allowed developing GPS based application for navigation and mapping and easily provides the location information from anywhere. The Land Map Android Application & Web Server are proposed in this work which is capable of providing land information along with the owner certificates.